2017
DOI: 10.1051/kmae/2017001
|View full text |Cite
|
Sign up to set email alerts
|

The invertebrate community of the chalk stream hyporheic zone: spatio-temporal distribution patterns

Abstract: -This study examined the longitudinal distribution, vertical distribution and temporal dynamics of the invertebrate community inhabiting the chalk hyporheic zone of four catchments, which differed in their degree of eutrophication and sediment composition. We characterised the invertebrate community at two depths (20 and 35 cm), in the heads and tails of riffles at low and high groundwater levels. Taxon density declined significantly with increasing depth. The abundance of invertebrates did not differ signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In fact, the reduction in density of large organisms through depth has been broadly reported as a general pattern in studies of riverbed communities (i.e. Dole-Olivier et al 1994, Marchant, 1995, Maridet & Philippe 1995, Davy-Bowker et al 2006, Pacioglu & Robertson 2017). Accordingly, it might be hypothesized that the depth gradient, as a set of different physicochemical factors, is also a key variable causing the decline of biomass and secondary production of riverbed systems.…”
Section: Hyporheic Zone As a Budget Of Biomass And Production In Strementioning
confidence: 93%
“…In fact, the reduction in density of large organisms through depth has been broadly reported as a general pattern in studies of riverbed communities (i.e. Dole-Olivier et al 1994, Marchant, 1995, Maridet & Philippe 1995, Davy-Bowker et al 2006, Pacioglu & Robertson 2017). Accordingly, it might be hypothesized that the depth gradient, as a set of different physicochemical factors, is also a key variable causing the decline of biomass and secondary production of riverbed systems.…”
Section: Hyporheic Zone As a Budget Of Biomass And Production In Strementioning
confidence: 93%
“…Most of the taxonomic groups collected from the Dagua River (Table 2) have been reported by various authors in different locations worldwide (e.g., Barrera González et al, 2014;Boon et al, 2016;Di Lorenzo et al, 2013 & Levei, 2015; Mugnai et al, 2015a;Pacioglu & Robertson, 2017;Peralta-Maraver et al, 2018;Pérez Fernández & Pérez Ruiz, 2015;Pryce et al, 2010;Stubbington et al, 2016;Tione et al, 2014). In the Neotropical region, Fernández (2002) and Fernández and Fossati-Gaschignard (2011) registered the Hydrachnidia and Oligochaete (Rodríguez, 2002) groups.…”
Section: Hyporheic and Macrobenthic Faunamentioning
confidence: 88%
“…High CNESS dissimilarity values in this context reflect a low probability that two samples are drawn from the same community. For low values of m (the sample size parameter) the similarity between samples is strongly determined by dominant species, whereas for high values, the composition of the entire species assemblage becomes increasingly important [33]. CNESSa values were obtained using the R function from Zou and Axmacher [39], which is a standardized version of CNESS dissimilarity where values range between 0 (samples are the same) and 1 (samples are 100% different).…”
Section: Discussionmentioning
confidence: 99%
“…With the pump shaft inserted to 30 cm below river bed level, five litres of river water after [29,30] were extracted at five locations at each site (five replicates per sampling occasion). A 30 cm depth was selected because previous studies on the Lambourn [31] and on other chalk streams have shown that the hyporheic zone is very shallow compared to rivers draining other geologies, e.g., [32,33]. The locations of sampling points were approximately ten meters apart, zig-zagging across the river.…”
Section: Samplingmentioning
confidence: 99%